PERENCANAAN SALURAN DRAINASE BERSUMUR RESAPAN DI LINGKUNGAN KAMPUS UNIVERSITAS DIPONEGORO TEMBALANG-SEMARANG - Daru Kumala wibihestusri; Hamanda Arief Wiranaba; Priyo Nugroho P.; Dwi Kurniani (Jurnal Karya Teknik Sipil, 2013)
The problem that often happen nowadays is flood in rain season and drought in dry season. The other problem is land degradation for infiltrating water caused by environment changes which is land development effect. One of problem solving and ground water conservation effort at Diponegoro University Campus Area is to build drainage with infiltration well. This drainage with infiltration well is expected to reduce run off water caused by development at Undip campus area. This designing process does the hidrology analysis with rainfall data for 15 years at Sta. Gunungpati, Sta. Banyumeneng, and Sta. Pucanggading. The hidrology analysis for this design use normal probability distribution and rational method with rain repeat period 2 year. This hidrology analysis results are post-development flow (Qpascapembangunan) 4,633 m3/s and pre-development flow (Qprapembangunan) 2,357 m3/s so it can be know that development caused increasing flow (∆Q) 2,277 m3/s. The analysis result is used to design the drainage channel and infiltration well. In this design, the drainage channel at Undip campus is still good to use so it is just need to build infiltration well. Infiltration well dimension is 0,5 m diameter, 1,2 m depth and 3 m length between infiltration wells. There is water catchment box and infiltration well’s cover on the top each infiltration well. Water catchment box dimension is 0,8 m length, 0,8 m width and 0,1 m height, while infiltration well’s cover dimension is 0,6 m diameter and 5 cm width. The existencies of drainage with infiltration well can absorb water about 11,885 % from run off flow caused by development (the differential flow between pre-development and post-development) , that calculated with method for Research Effect of Hydrology and Hydraulic Caused by Infiltration Well Combination at Drainage System with infiltration well condition. To determine the effectiveness of the water absorption from infiltration well, this study is calculated water absorption for a year in 2011. This calculation is using two intensity approaching methods, namely: Mononobe Method and Alternating Block Method (ABM). From these calculations predicted drainage with infiltration well that can absorb water 12.051% - 43.660% of the discharge rain, so the volume of absorbed water reach 600,000 m3.